РАЗВИВАНЕ НА КОГНИТИВНИ И МЕТАКОГНИТИВНИ УМЕНИЯ ЗА ЧЕТЕНЕ В ОБУЧЕНИЕТО ПО БЪЛГАРСКИ ЕЗИК ЧРЕЗ РАБОТА С УЧЕБНИ ЗАДАЧИ - Василева, Деспина (Bulgarian Language & Literature / Bulgarski Ezik i Literatura, 2022)
The presented article deals with the problem of developing cognitive and metacognitive skills for reading and also for solving learning tasks in Bulgarian language classes. Cognitive skills refer to the learning activities. When working with text, they are related to the student's ability to extract information from text and construct meaning from what is read. Metacognitive skills include the volitional tracing of one's own reading patterns. Cognitive reading skills are systematized in four groups: (1) skills for extracting information from text, (2) skills for interpretation, (3) skills for critical reflection, and (4) skills for working with text presented on a screen. A study of assessment given by teachers of Bulgarian language on the degree of acquisition of cognitive and metacognitive skills by students in lower secondary and upper secondary education in reading text and solving learning problems is presented. Cognitive skills are divided into four groups - for extracting information from text; for interpretation; for critical reflection; and for working with text on a screen. The obtained results demonstrated that teachers rate as more developed the skills for extracting information from text than those for interpretation, critical reflection, and working with text on a screen. There is no real (statistical significant) difference between cognitive and metacognitive skills in assessing the level of skills developed when working with learning tasks.